2010
DOI: 10.1007/s10765-010-0798-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Ag and Ag–Cu Liquid Alloys at 1098K to 1573K

Abstract: The surface tension and density of liquid Ag and Ag-Cu alloys were measured with the sessile drop method. The sessile drop tests were carried out at temperatures from 1098 K to 1573 K, on cooling (temperature decreasing stepwise) under a protective atmosphere of high purity Ar (6N). The density of liquid Ag and Ag-Cu alloys decreases linearly with increasing temperature, and an increase in concentration of copper results in a lower density. The surface tension dependence on temperature can be described by line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Moreover, the surface tension increases with increasing Cu content. These observations are in accord in behavior and magnitude with the reported experimental data [31] (Fig. 2).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the surface tension increases with increasing Cu content. These observations are in accord in behavior and magnitude with the reported experimental data [31] (Fig. 2).…”
Section: Resultssupporting
confidence: 92%
“…2). As seen, the slopes in Table 2 illustrates the calculated values and various literature data [13][14][15][16][17]31,32] of the surface tension of Ag x−1 -Cu x liquid alloys as a function of x Cu (0-1), at 1373 K. With this comparison, it observed that, in all cases, the surface tension of the alloy increases with an increase in copper content. The calculated values agree remarkably with the experimental mea- Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…(3 -5). The excess surface tension for each binary system Ex ij was calculated at 1 173 K based on the surface tension data for: Sn -Ag [14 -17], Ag -Cu [18 -20], Sn -Cu [16,21,22] and the data for pure components [20,23,24]. The calculated Ex ij for each system was described with the Redlich-Kister (R -K) polyno- mial [25], and the polynomial parameters A i for each binary system are collected in Table 2.…”
Section: Surface Tension: Experiments and Modelmentioning
confidence: 99%
“…For a ternary mixture, the relation between the surface tension of an alloy, the surface tension the component i, and the thermodynamic properties of the component i in the bulk and in the surface phase, can also be shown by means of Butler equation [26]: [27] based on the Butler equation, which utilizes the density and surface tension of pure metals Sn [23,24], Ag [20], Cu [19,24], as well as the thermodynamic properties of limiting binary alloys (Sn -Ag, Sn -Cu, Ag -Cu) [28], the surface tension of the Sn -Ag -Cu alloys was calculated and the results are presented in Fig. 5.…”
Section: Surface Tension: Experiments and Modelmentioning
confidence: 99%